Modification of thermal chemical rates in a cavity via resonant effects in the collective regime - Sun, Jing; Vendrell, Oriol (The journal of physical chemistry letters, 2023)
The modification of thermal chemical rates in Fabry-Perot cavities, as observed in experiments, still poses theoretical challenges. While we have a better grasp of how the reactivity of isolated molecules and model systems changes under strong coupling, we lack a comprehensive understanding of the combined effects and the specific roles played by activated and spectator molecules during reactive events. In this study, we investigate an ensemble of randomly oriented gas-phase HONO molecules undergoing a cis-trans isomerization reaction on an ab initio potential energy surface. One thermally activated molecule can overcome the reaction barrier, while the other molecules are nonactivated but coupled to the cavity as well. Using the classical reactive flux method, we analyze the transmission coefficient and determine the conditions that lead to accelerated rates within the collective regime. We identify two main mechanistic aspects: First, nonactivated molecules enhance the cavity’s ability to dissipate excess energy from the activated molecule postreactive event. Second, the activated molecule couples with the polaritonic resonance created by the nonactivated molecules and the cavity at a shifted resonance frequency with respect to the bare cavity.
Gesehen am 18.01.2024